Characterising and representing small crack growth in an additive manufactured titanium alloy. (August 2021) - Shamir, Muhammad; Zhang, Xiang; Syed, Abdul Khadar
Highlights: The modified Hartman-Schijve equation is used for predicting small crack growth rate. Material constants in the equation can be fitted by long crack test data alone. Small crack is modelled by setting the stress intensity factor threshold to a small value. Small crack growth rate in 3D printed titanium was measured for model validation. Predicted small crack growth life in another specimen geometry agreed well with test. Abstract: The purpose of the research is to apply the modified Hartman-Schijve equation for predicting small crack growth rate in an additive manufactured titanium Ti-6Al-4V. Material constants in the equation were determined by long crack test data, and the threshold value of the stress intensity factor range was set to a small value. A small fatigue crack test was conducted to validate the fitted equation. Predicted fatigue life of another specimen configuration under bending load agreed well with the test result. The work shows that it may be possible to represent both small and long crack growth rates by the modified Hartman-Schijve equation with its material constants being determined by long crack test.